Centaurea goksivriensis (Asteraceae), a new species from Turkey - Bona, Mehmet (Phytotaxa, 2015)
Centaurea goksivriensis M. Bona, a new species of C. sect. Acrocentron from Hatay Province of Turkey, is described and illustrated. It is morphologically similar to C. antiochia var. antiochia, C. carduiformis, and C. urvillei subsp. armata but differs mainly in its flower colour, indumentum and pappus. The IUCN conservation status of Critically Endangered (CR) should be applied to C. goksivriensis.